2017
DOI: 10.1111/1475-6773.12797
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Patterns in Cesarean Delivery Scheduling and Timing in Oregon before and after a Statewide Hard Stop Policy

Abstract: Oregon's hard stop policy limiting elective early-term cesarean delivery was associated with lower odds of cesarean delivery in the category of women who were targeted by the policy; more research is needed on impact of such policies on neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The comparative interrupted time series approach combines the strengths of several quasi‐experimental approach (ie, ITS and difference‐in‐differences), by controlling for secular time trends before and after policy implementation, and comparing the policy group to a control group that is not exposed to a similar policy 39 . Although the policy was implemented at a single time (October 1, 2009), prior research on this policy and others has demonstrated gradual changes in childbirth care after implementation of policy changes, 10,19,30,31 so we targeted the postpolicy quarterly time‐trend as our effect of interest, rather than the postpolicy level difference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative interrupted time series approach combines the strengths of several quasi‐experimental approach (ie, ITS and difference‐in‐differences), by controlling for secular time trends before and after policy implementation, and comparing the policy group to a control group that is not exposed to a similar policy 39 . Although the policy was implemented at a single time (October 1, 2009), prior research on this policy and others has demonstrated gradual changes in childbirth care after implementation of policy changes, 10,19,30,31 so we targeted the postpolicy quarterly time‐trend as our effect of interest, rather than the postpolicy level difference.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis was based on the findings that a greater share of cesareans among black women are performed without medical indication 9,11 and are amenable to prevention. Changes in childbirth care have been documented to occur gradually rather than immediately in response to changes in policy and care recommendations, 10,30,31 so we hypothesized that reductions would accrue gradually in the postpolicy period, resulting in a potential trend change, rather than an immediate drop after the policy. Results from this analysis may help further explain how policies and social context (including structural racism) may translate into racial inequities, a topic of particular relevance in maternal health 13,32 .…”
Section: Introductionmentioning
confidence: 99%
“…(42) The study from Snowden et al resulted in another publication by Muoto et al and is an additional analysis. (37,46) We used the rst publication by Snowden et al and added outcome data from the subsequent publication. All studies included women with elective CS which was safe for mother and neonate to be postponed from 37 + 0-38 + 6 WG to ≥ 39+(0-6) WG.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Increasing awareness of the potential adverse consequences of LPET delivery, together with rising rates of LPET births during the late 20th and early 21st centuries [52][53][54][55], led to the development of various policies and initiatives aimed at minimising planned deliveries at these gestations. However, despite some significant reductions [49,[56][57][58][59][60][61][62][63][64], the number of LPET births remains high. In 2021, almost 33,700 late preterm and more than 151,500 early term births were recorded in England and Wales [65].…”
Section: Introductionmentioning
confidence: 99%